Melanin synthesis using some bacteria isolated from marine sediments - زوان, ميس; أحمد قره علي ,; ياسر حماد,; بدر العلي , (Latakia University Journal -Biological Sciences Series, 2024)
Melanin is one of the important biological dyes produced by organisms, especially bacteria, as it plays an important role in the ecosystem and the life of organisms, and has an important role in various fields (food, pharmaceutical, industrial and others). In this study, the melanin-producing bacteria strain MKa1 was isolated and purified from the marine sediment of the estuary of Alkaber Alshemali River in Latakia on the medium of Agar-Tyrosine. This bacterial strain showed a clean zone around its colony and this means that it is melanin-positive. Next, melanin was produced using MKa1 bacteria in broth-tyrosine medium and incubated at 37°C for 30 days, then the production medium was centrifuged, and the concentration of melanin produced in the medium was determined using a specterophytometer at 400 nm. The functional groups of the produced melanin were identified using the Fourier-transform infrared spectroscopy (FTIR). The results showed that the FTIR spectrum of the melanin molecule produced using MKa1 bacteria matched the FTIR spectrum of the standard melanin molecule, which confirms the importance of this research in the production of bioactive melanin using the bacterial strain MKa1 isolated from marine sediments.